Nice to meat you - Ng, Brenlyn Jie Jia (Nanyang Technological University, 2020)
Nice to Meat You is a Final Year Project drama film produced by Nicholas Teo, Natasha Wee, Darrell Er and Brenlyn Ng under the supervision of Ms Sheersha Perera as undergraduates of the Wee Kim Wee School of Communication and Information. This report aims to provide insight into our short film by explaining the rationalisations and key considerations that went into the creative processes from the initial conceptualisation to post-production.